A function
f
(
x
)
is defined as
f
(
x
)
=
{
1
0
if
0
≤
x
≤
1
otherwise
Consider n random variables X 1 , X 2 , … … X n such that f ( x ) is probability distribution function of each of the random variables i.e., ∀ X i ; i = 1 , 2 , … , n , f ( x ) is the probability distribution function.
Let E n denote the n th power of the expected value of max { X 1 , X 2 , … … X n } .
As n grows larger, the expression E n is found to converge to E .
Evaluate ⌊ 1 0 0 0 E ⌋ .
Details and Assumptions:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Without loss of generality let us consider the case when :- X n > X n − 1 > X n − 2 > . . . . . > X 2 > X 1
In this case max { X 1 , X 2 . . . X n } = X n
Now calculating the expected value we have :- ∫ 0 1 ∫ X 1 1 ∫ X 2 1 . . . . . . ∫ X n − 1 1 X n d X n d X n − 1 . . . . d X 3 d X 2 d X 1 = ( n + 1 ) ! n
(The integration is not very difficult. You can maybe take the case for n= 3 or 4 and then prove by induction).
Now there are n ! such ordered n-tuples of X 1 , X 2 . . . X n . So there are n ! ways to arrange them in descending order. Each of them will have equal probabilities and hence equal expected values for the maximum of the n random variables. Hence by total probability we have the expected value is n ! ⋅ ( n + 1 ) ! n = n + 1 n .
So raising it to the nth power and taking the limit as n → ∞ we have the answer as e 1 .
(Note we can also do it by considering the minimum of the n variables . In that case the integral would be a little easier. Then we can just substract it from 1 to get the expected value of maximum of n variables.)
Problem Loading...
Note Loading...
Set Loading...
From the pdf of X , we know that X i ∼ U ( 0 , 1 ) ∀ i . Given this, the cdf of Y n , where Y n = 1 ≤ i ≤ n max X i is:
F ( y ) = ( ∫ 0 y d t ) n = ( t ∣ 0 y ) n = y n , 0 ≤ y ≤ 1
The pdf of Y n is given by the derivative of the its cdf, which is f ( y ) = n y n − 1 , 0 ≤ y ≤ 1 .
Thus, E [ Y n ] = ∫ 0 1 n y n d y = n + 1 n y n + 1 ∣ ∣ ∣ ∣ 0 1 = n + 1 n . And given this, E n = ( n + 1 n ) n .
E = n → ∞ lim ( n + 1 n ) n
= n → ∞ lim ( 1 − n + 1 1 ) n
= m → ∞ lim ( 1 − m 1 ) m − 1
= m → ∞ lim ( 1 − m 1 ) ( 1 − m 1 ) m
= 1 e − 1 = e 1
Thus, ⌊ 1 0 0 0 E ⌋ = ⌊ e 1 0 0 0 ⌋ = 3 6 7 .